A Higher Dosage of Oral Alendronate Will Increase the Subsequent Cancer Risk of Osteoporosis Patients in Taiwan: A Population-Based Cohort Study - Lee, Wen-Yuan (Public Library of Science, 2012)
BACKGROUND: Controversy still exists regarding whether alendronate (ALN) use increases the risk of esophageal cancer or breast cancer. METHODS: This paper explores the possible association between the use of oral ALN in osteoporosis patients and subsequent cancer risk using the National Health Insurance (NHI) system database of Taiwan with a Cox proportional-hazard regression analysis. The exposure cohort contained 5,624 osteoporosis patients used ALN and randomly frequency-matched by age and gender of 3 osteoporosis patients without any kind of anti-osteoporosis drugs in the same period. RESULTS: For a dose ≥1.0 g/year, the risk of developing overall cancer was significantly higher (hazard ratio: 1.69, 95% confidence ratio: 1.39–2.04) than in osteoporosis patients without any anti-osteoporosis drugs. The risks for developing liver, lung, and prostate cancers and lymphoma were also significantly higher than in the control group. CONCLUSIONS: This population-based retrospective cohort study did not find a relationship between ALN use and either esophageal or breast cancer, but unexpectedly discovered that use of ALN with dose ≥1.0 g/year significantly increased risks of overall cancer incidence, as well as liver, lung, and prostate cancers and lymphoma. Further large population-based unbiased studies to enforce our findings are required before any confirmatory conclusion can be made.